Challenges of Implementing the Independent Curriculum in the Digital Era for Strengthening Students’ Character Values: A Literature Review - Ibrahim; Windy Yulistiani; Indah Juni Yanti; Intan Nuraini; Bambang Irawan (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2026)
The Independent Curriculum provides flexibility for educators to develop student-centered learning, including the strengthening of character values in accordance with the Pancasila Student Profile. However, the digital era presents new challenges, such as low levels of teachers’ information technology competence, limited infrastructure, unequal access to technology, and weak supervision of students’ gadget use. This study employs a literature review method by examining scientific journals, academic articles, books, research reports, and official policy documents published between 2019 and 2024. The analysis is conducted descriptively by identifying key themes related to the challenges and opportunities for strengthening character through the Independent Curriculum in the digital era. The results and discussion indicate that the main challenges include limited teachers’ digital literacy, disparities in facilities among schools, minimal collaboration between schools and parents, and difficulties in integrating character values into digital learning. Nevertheless, technology has the potential to support character internalization through interactive learning media, digital projects based on the Pancasila Student Profile, collaborative platforms, and ethical digital literacy. Strategies for strengthening character include integrating character values into digital learning design, technology-based learning models, meaningful digital literacy, teachers’ digital role modeling, school–parent collaboration, and digital-based school programs. Improving teacher competence, ensuring equitable facilities, and fostering synergy with families are key to the successful implementation of this curriculum. Keywords: Digital Era, Independent Curriculum, Students’ Character. Abstrak: Kurikulum Merdeka memberikan keleluasaan bagi pendidik untuk mengembangkan pembelajaran yang berpusat pada siswa, termasuk penguatan nilai karakter sesuai Profil Pelajar Pancasila. Penelitian ini menggunakan metode kajian literatur dengan menelaah jurnal ilmiah, artikel akademik, buku, laporan penelitian, dan dokumen kebijakan resmi yang diterbitkan antara tahun 2019–2024. Analisis dilakukan secara deskriptif dengan mengidentifikasi tema utama terkait tantangan dan peluang penguatan karakter melalui Kurikulum Merdeka di era digital. Berdasarkan hasil dan pembahasan bahwa tantangan utama meliputi keterbatasan literasi digital guru, kesenjangan fasilitas antar sekolah, minimnya kolaborasi sekolah orang tua, serta kesulitan mengintegrasikan nilai karakter ke dalam pembelajaran digital. Meski demikian, teknologi memiliki potensi mendukung internalisasi karakter melalui media pembelajaran interaktif, proyek digital berbasis Profil Pelajar Pancasila, platform kolaboratif, dan literasi digital yang etis. Strategi penguatan karakter mencakup integrasi nilai karakter dalam desain pembelajaran digital, model pembelajaran berbasis teknologi, literasi digital bermakna, keteladanan digital guru, kolaborasi sekolah–orang tua, dan program sekolah berbasis digital. Peningkatan kompetensi guru, pemerataan fasilitas, dan sinergi dengan keluarga menjadi kunci keberhasilan implementasi kurikulum ini. Kata Kunci: Era Digital, Kurikulum Merdeka, Karakter Peserta Didik.